Criminal Liability for Defendants Who Commit Crimes in the Field of Medical Practice - Firdaus, Firdaus; Tiara, Dora; Viana, Wira Okta (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
Physicians and dentists knowingly practising medicine without a practice license are subject to penalties under Article 76 of Law Number 29 of 2004 concerning Medical Practice. These penalties can include up to three years in prison or a fine of up to IDR 100,000,000..00 (one hundred million rupiah). The defendant, Putri Regita Yuniar, was referred to as Putri Binti, the late Edward Sebastian, in Decision Number 598/Pid.Sus/2022/PN.Pdg. The problem is formulated as follows: First, based on Decision Number 598/Pid.Sus/2022/PN.Pdg, what factors does the court consider when rendering a criminal decision for offences in the medical practice area? Second, according to Decision Number 598/Pid.Sus/2022/PN.Pdg, what is the criminal liability of defendants who commit offences in the medical practice area? This research's specifications are descriptive. This thesis was written using a normative juridical method. This study exclusively employed secondary data sources. The collected data was given descriptively after undergoing qualitative analysis. The following conclusions can be drawn from the research and discussion: first, the judge's factors when rendering a criminal decision for criminal acts in the medical practice area are classified as non-juridical factors, which include the defendant's aggravating and mitigating circumstances, and juridical factors, which are based on information presented during the trial, including the public prosecutor's indictment, witness statements, and the defendant's statements. Second, the defendant Putri Regita Yuniar, also known as Putri Binti, the late Edward Sebastian, was condemned by Law Number 29 of 2004 concerning Medical Practice, Article 78 in connection with Article 73 paragraph (2).